Tranexamic Acid for the Prevention and Treatment of Postpartum Hemorrhage. Issue 1 (March 2016) - Sentilhes, L.; Lasocki, S.; Ducloy-Bouthors, A.S.; Deruelle, P.; Dreyfus, M.; Perrotin, F.; Goffinet, F.; Deneux-Tharaux, C.
Abstract : ( Br J Anaesth. 2015;114 (4):576–87) Postpartum hemorrhage (PPH) accounts for one quarter of all maternal deaths worldwide, and uterotonic agents are currently used to treat the condition. Treatment could be enhanced through the use of prohemostatic drugs. Tranexamic acid can be used as complementary therapy to uterotonic agents for the treatment of PPH. This review evaluated the effectiveness of tranexamic acid for the prevention and treatment of PPH after cesarean and vaginal deliveries, as well as the drug's possible side effects.